2017
DOI: 10.1039/c7ra09567h
|View full text |Cite
|
Sign up to set email alerts
|

The effects of He clusters on the mechanical properties of Ti3AC2 (A = Ge, Si): first-principles studies

Abstract: Herein, the damage to the mechanical properties of Ti 3 AC 2 (A ¼ Ge, Si) was systematically investigated by first-principles calculations. It is known that the interstitial He atoms homogenously generated in the materials would finally migrate to the A layer and form clusters of no more than 7 He atoms at a monovacancy in the A layer, and the cluster of 7 He atoms reduces the ideal tensile strength of Ti 3 SiC 2 (or Ti 3 GeC 2 ) to about 37.3% (or 35.5%). The strain simulations showed that the fracture would … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Therefore, the dissolved He atoms are expected to aggregate in the low potential area where staying near the Al layer in perfect Cr 2 AlC at the early stage of helium irradiation. Based on the first principle calculations on He migrating and clustering in Ti 3 SiC 2, it has been found that He atom most easily occupies the octahedral interstitial site near Si layer and then hexahedral site in the Si layer (their difference in solution energies is only 0.01 eV), and they will diffuse along Si atom plane with very small diffusion barrier of 0.05 eV. As a consequence, with the increasing of doped He, they aggregate in the Si layer and form the He clusters with pre‐existing vacancies or vacancies produced in the process of ion irradiation (Si layer has smallest forming energy of vacancy).…”
Section: Calculation Results and Discussionmentioning
confidence: 99%
“…Therefore, the dissolved He atoms are expected to aggregate in the low potential area where staying near the Al layer in perfect Cr 2 AlC at the early stage of helium irradiation. Based on the first principle calculations on He migrating and clustering in Ti 3 SiC 2, it has been found that He atom most easily occupies the octahedral interstitial site near Si layer and then hexahedral site in the Si layer (their difference in solution energies is only 0.01 eV), and they will diffuse along Si atom plane with very small diffusion barrier of 0.05 eV. As a consequence, with the increasing of doped He, they aggregate in the Si layer and form the He clusters with pre‐existing vacancies or vacancies produced in the process of ion irradiation (Si layer has smallest forming energy of vacancy).…”
Section: Calculation Results and Discussionmentioning
confidence: 99%
“…The MAX phases are nanolaminated ceramics with the Mn+1AXn general stoichiometry, where typically 'M' corresponds to an early transition metal, 'A' is an element from groups 13-15 in the periodic table, 'X' is either C or N, and n = 1, 2 or 3 [1]. For nuclear applications close to the reactor core, N is not preferred as an X candidate element to avoid formation of the longlived isotope 14 C. The hexagonal close-packed (hcp) unit cell of the MAX phases consists of 'n' number of M6X octahedral "ceramic" building blocks interleaved by single atomic layers of the "metallic" 'A' element. Solid solutions on the M and A sites broaden the compositional range of the MAX phases that can be synthesised and tailored in order to meet the property requirements of the targeted application.…”
Section: Introductionmentioning
confidence: 99%
“…The MAX phases are steadily gaining attention for select envisaged nuclear applications, and a number of He irradiation studies on the MAX phases have already been reported in the open literature -for example on Ti3AlC2 [5,[9][10][11][12][13][14][15][16], Ti2AlC [17][18][19], Ti3SiC2 [6,[20][21][22], Cr2AlC [23,24], V2AlC [25], and Ti4AlN3 [19]. Overall, the He irradiation of MAX phase compounds tends to result in He atoms residing preferentially in the A-layer, thereby dislocating A-elements from their original sites [6,10,12,13,18,20,21].…”
Section: Introductionmentioning
confidence: 99%